Manajemen Mutu Terpadu - Sriwidadi, Teguh (Journal the Winners: Economics, Business, Management, and Information System Journal, 2001)
Total Quality Management (TQM) is the effort to meet or exceed the customer needs with the lowest cost. The business will successful if it can produce an output (product and service) fit according to the customer needs. They will raise the profit if only they can operate efficiently (effective cost, avoid waste, and rework ), and to ensure that all the activity directed to the effort to satisfy the customer needs.